Pemanfaatan Kardus menjadi Kotak Tissue yang Mempunyai Nilai Seni yang Tinggi - Arnaya; Umra; Nur Ainun; Karmila Anwar; Sapar; Ilham Tahier; Ratna Wati (Jurnal Ilmiah Pengabdian dan Inovasi, 2023)
A tissue box is a must have on coffee tables and kitchens. This will make it easier to find tissues. Utilization of used cardboard as a basic material for making tissue boxes that are widely used by the community by creating goods made from used cardboard into items that have a selling price value. So that the cardboard is not thrown away. Therefore, by making our own modern tissue box, we can save costs. Because it can be made using unused materials. The method used in carrying out this business activity is based on input, process, output (product), and evaluation. The product made in this student creativity program is a Tissue Box which is very useful as an interior. This product is safe to use for a long time.